The form and content of modern english music and its apllication as a teaching tool in the classroom - Morocho, José (2010)
Music has many purposes from communication, entertainment, and cultural ceremonial practices, therefore, could we not consider music as a useful teaching tool, one with which to learn about language, people and society? The purpose of this research work is to discover not only the effects of music and song in the foreign language classroom, but also to analyze the content, form and message delivered through the lyrics and to determine if popular modern English language is a suitable teaching tool in the English foreign language classroom.